K‐distribution three‐dimensional mapping of biological tissues in optical coherence tomography. Issue 3 (4th October 2017) - Sugita, Mitsuro; Brown, Robert A.; Popov, Ivan; Vitkin, Alex
Abstract : Probability density function (PDF) analysis with K‐distribution model of optical coherence tomography (OCT) intensity signals has previously yielded a good representation of the average number of scatterers in a coherence volume for microspheres‐in‐water systems, and has shown initial promise for biological tissue characterization. In this work, we extend these previous findings, based on single point M‐mode or two‐dimenstional slice analysis, to full three‐dimensional (3D) imaging maps of the shape parameter α of the K‐distribution PDF. After selecting a suitably sized 3D evaluation window, and verifying methodology in phantoms, the resultant parametric α images obtained in different animal tissues (rat liver and brain) show new contrasting ability not seen in conventional OCT intensity images. Abstract : A novel contrast for optical coherence tomography (OCT) exploiting light scattering statistics in random media is reported. The K‐distribution modeling for the intensity signal of OCT, represented by the shape parameter α, is applied to three‐dimensional image data acquired in ex‐vivo rat liver and brain. The resultant parametric α‐maps depict interesting differences in tissue regions that appear homogeneous on regular OCT structural intensity images.